2022
DOI: 10.3390/molecules27217466
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Beneficial Effects of Ursolic Acid against Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths globally. Despite current treatment approaches that include surgery, chemotherapy, radiation and immunotherapies, lung cancer accounted for 1.79 million deaths worldwide in 2020, emphasizing the urgent need to find novel agents and approaches for more effective treatment. Traditionally, chemicals derived from plants, such as paclitaxel a nd docetaxel, have been used in cancer treatment, and in recent years, research has focused on finding other plant-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Our study has shown that bearberry leaves are another source of compounds with proapoptotic activity against gliomas and that the Et extract has much higher anticancer activity than Aq (Figures 2 and 3). Additionally, ethanolic extracts contain UA and OA (Table 1), which are characterized by anticancer activity against different types of cancer [38,60,61]. Attention should also be paid to the chemical profile of Aq characterized by higher contents of HQ and COR in comparison with Et but, above all, to the negative correlation between HQ-Ap and COR-Ap in the two studied cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that bearberry leaves are another source of compounds with proapoptotic activity against gliomas and that the Et extract has much higher anticancer activity than Aq (Figures 2 and 3). Additionally, ethanolic extracts contain UA and OA (Table 1), which are characterized by anticancer activity against different types of cancer [38,60,61]. Attention should also be paid to the chemical profile of Aq characterized by higher contents of HQ and COR in comparison with Et but, above all, to the negative correlation between HQ-Ap and COR-Ap in the two studied cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…These data together strongly suggested that the effects by UA treatment on AR expression and signaling is likely through its inhibition of RORγ function in the PCa cells. Several studies showed that UA can inhibit cancer cell and tumor growth by interfering with cell cycle, proliferation, apoptosis, inflammation, angiogenesis, and metastasis ( Iqbal et al, 2018 ; Kornel et al, 2022 ; Zafar et al, 2022 ). However, there has been no evidence showing that UA can affect AR expression and/or AR signaling, which is the key driver of PCa development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…UA modulates different pharmacological pathways, leading to multifaceted health benefits and the prevention of chronic diseases [23,55,56]. In fact, UA demonstrated antiproliferative effects against hepatocellular carcinoma [57,58], lung cancer [59,60], leukemia [61][62][63], breast cancer [64,65], prostate and urogenital cancers [66,67], and cervical cancer [68,69].…”
Section: Peer Review 2 Of 19mentioning
confidence: 99%